A Novel Missense Mutation of Arginine Vasopressin Receptor 2 in a Chinese Family with Congenital Nephrogenic Diabetes Insipidus: X-Chromosome Inactivation in Female CNDI Patients with Heterozygote 814A>G Mutation. (12th July 2022) - Zang, Li; Gong, Yuping; Li, Yijun; Dou, Jingtao; Lyu, Zhaohui; Su, Xiaoqing; Zhang, Yawei; Mu, Yiming
Abstract : Background . To identify novel clinical phenotypic signatures of congenital nephrogenic diabetes insipidus (CNDI). Methods . A Chinese family with CNDI was recruited for participation in this study. The proband and one of his uncles suffered from polydipsia and polyuria since infancy. The results of clinical testing indicated the diagnosis of CNDI. 10 family members had similar symptoms but did not seek medical advice. Genetic testing of mutations in the coding region of the aquaporin 2 ( AQP2 ) gene and the arginine vasopressin receptor 2 ( AVPR2 ) gene were carried out in 11 family members. Somatic DNA from 5 female family members was used to test for methylation of polymorphic CAG repeats in the human androgen receptor (AR) gene, as an index for X-chromosome inactivation pattern (XCIP). Results . AQP2 gene mutations were not found in any family members, but a novel missense mutation (814th base A>G) in exon 2 of the AVPR2 gene was identified in 10 individuals. This mutation leads to a Met 272 Val (GAT-GGT) amino acid substitution. Skewed X-chromosome inactivation patterns of the normal X allele were observed in 4 females with the AVPR2 gene mutation and symptoms of diabetes insipidus, but not in an asymptomatic female with the AVPR2 gene mutation. Conclusions . Met 272 Val mutation of the AVPR2 gene was identified as a novel genetic risk factor for CDNI. The clinical NDI phenotype of female carriers with heterozygous AVPR2 mutation may be caused by X-chromosome inactivation induced by dominant methylation of the normal allele of AVPR2 gene.